Tag Cloud for Visualized Advertisements - Ozger, Zeynep Banu; Bayiroglu, Hacer (IEEE, 2018)
Tag clouds are a popular way to visualize data in web sites or documents using text properties such as font size, color, and so on. In areas with a wide range of workplaces, the ability of employers to access the skills they are looking for more easily helps the decision makers in the field to decide where they need to improve themselves. In this study, through a very popular employment site in Turkey, skills sought after for a specific profession have been visualized using a tag cloud.
Keywords: data visualization; tag cloud; information extraction; content summarization; Computer Science; Engineering